Penerapan safety talk sebagai upaya pencegahan kecelakaan kerja terhadap petugas unit pelayanan teknik di PT. PLN - Rahma Oktaria; Dwi Noerjoedianto; David Kusmawan; Oka Lesmana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Occupational safety and health (OSH) is a crucial aspect in creating a safe work environment and preventing workplace accidents. One example of OSH implementation in a company is the implementation of safety socialization as a means of communicating occupational safety before work begins. The state electricity company procurement service unit in Kota Baru Jambi routinely conducts safety outreach as part of its efforts to increase worker awareness and discipline regarding occupational safety. Purpose: To determine the policy and implementation of safety socialization, as well as the challenges, obstacles, and successes of safety socialization implementation at state electricity company. Method: This qualitative research uses a case study approach to in-depth examine the implementation of safety socialization as an effort to prevent workplace accidents. This research was conducted at State Electricity Company procurement service unit in Kota Baru Jambi, Jelutung District, Jambi City, since November 2025. Seven informants were selected using a purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation of informants involved in safety socialization. Results: Safety discussions have been routinely implemented and integrated into the company's operational activities. The implementation of safety discussions has contributed to increasing worker awareness regarding the use of personal protective equipment (PPE) and compliance with work safety procedures. Challenges encountered include differences in worker understanding, time constraints, and lack of participation from some workers. Other obstacles include monotonous delivery methods and one-way communication. Nevertheless, the implementation of safety discussions has shown positive results, marked by improved work discipline and a minimum of fatal workplace accidents. Conclusion: The implementation of safety discussions has been quite successful and has contributed to improving worker compliance with OSH procedures and preventing workplace accidents, although challenges remain in the delivery method, worker participation, and evaluation of their implementation. Suggestion: Future research should use more diverse methods, expand research locations, and examine other factors and the use of digital media to increase the effectiveness of safety discussions in supporting an OSH culture. Keywords: Occupational Accident Prevention; Occupational Safety and Health (OSH); Safety Discussions.